Is there inequity in hospital care among patients with acute coronary syndrome who are proficient and not proficient in English language?: Analysis of the SNAPSHOT ACS Study - Hyun, K; Redfern, J; Woodward, M; Briffa, T; Chew, D; Ellis, C; French, J; Astley, C; Gamble, G; Nallaiah, K; Howell, T; Lintern, K; et al. (Lippincott, Williams & Wilkins, 2016)
Background: The provision of equitable acute coronary syndrome (ACS) care in Australia and New Zealand requires an understanding of the sources of variation in the provision of this care. Objective: The aim of this study was to compare the variation in care and outcomes between ACS patients with limited English proficiency (LEP) and English proficiency (EP) admitted to Australian and NZ hospitals. Methods: Data were collected from 4387 suspected/confirmed ACS patients from 286 hospitals between May 14 and 27, 2012, who were followed for 18 months. We compared hospital care and outcomes according to the proficiency of English using logistic regressions. Results: The 294 LEP patients were older (70.9 vs 66.3 years; P ≺ .001) and had higher prevalence of hypertension (71.1% vs 62.8%; P = .004), diabetes (40.5% vs 24.3%; P ≺ .001), and renal impairment (16.3% vs 11.1%; P = .007) compared with the 4093 EP patients. Once in hospital, there was no difference in receipt of percutaneous coronary intervention (57.0% vs 55.4%; P = .78) or coronary artery bypass graft surgery (10.5% vs 11.5%; P = .98). After adjustment for medical history, there were no significant differences (P > .05) between the 2 groups in the risk of major adverse cardiovascular events and/or all-cause death during the index admission and from index admission to 18 months. Conclusions: These results suggest that LEP patients admitted to Australian or New Zealand hospitals with suspected ACS may not experience inequity in hospital care and outcomes.